Nobelovo nagrado za kemijo 2011 je prejel Danny Shechtman za odkritje kvazikristalov - Dolinšek, Janez (Obzornik za matematiko in fiziko, 2011)
Quasicrystals are materials having a new type of perfect long-range order without translational periodicity. Their symmetries (icosahedral, dodecagonal, decagonal, octagonal, and pentagonal) involve symmetry elements such as 5-, 8-, 10-, and 12-fold rotation axes, which are incompatible with the periodicity of a Bravais lattice. A consequence of nonperiodicity is that quasicrystals - alloys of matallic elements (Al-Pd-Mn, Al-Cu-Fe, Al-Ni-Co, Tb-Mg-Zn, etc.) - exhibit more semimetallic to insulating-like properties. Their favourable physical and mechanical properties - high hardness, resistance to corrosion and wear, low friction coefficient, low electrical and thermal conductivity, superplasticity at elevated temperatures, ability to store large ammounts of hydrogen - make quasicrystals interesting new materials for the technological application. Quasiperiodic symmetries are observed also in self-organized soft matter. The Nobel prize 2011 for chemistry was awarded to Israel scientist Danny Shechtman for the discovery of quasicrystals. This discovery has an interesting history, showing the difficulties of accepting a new breaktrough discovery in the scientific society.
Keywords: Danny Shechtman; kemija; kristalna mreža; kvazikristali; Nobelova nagrada; Shechtman, Danny